The Impact of Alcohol Consumption on Cardiovascular Health: Myths and Measures. Issue 1 (22nd July 2022) - Arora, Monika; ElSayed, Ahmed; Beger, Birgit; Naidoo, Pamela; Shilton, Trevor; Jain, Neha; Armstrong-Walenczak, Kelcey; Mwangi, Jeremiah; Wang, Yunshu; Eiselé, Jean-Luc; Pinto, Fausto J.; Champagne, Beatriz M.
Over the past several decades, the prevalence of cardiovascular disease (CVD) has nearly doubled, and alcohol has played a major role in the incidence of much of it. Alcohol has also been attributed in deaths due to infectious diseases, intentional and unintentional injuries, digestive diseases, and several other non-communicable diseases, including cancer. The economic costs of alcohol-associated health outcomes are significant at the individual as well as the country level. Risks due to alcohol consumption increase for most cardiovascular diseases, including hypertensive heart disease, cardiomyopathy, atrial fibrillation and flutter, and stroke. The widespread message for over 30 years has been to promote the myth that alcohol prolongs life, chiefly by reducing the risk of coronary heart disease (CHD). Lack of universal advice and stringent policy measures have contributed towards increased uptake and easy availability of alcohol. The WHO has called for a 10% relative reduction in the harmful use of alcohol between 2013–2025. However, lack of investment in proven alcohol control strategies, as well as persistence of misinformation and industry interference, have hindered the efforts of public health professionals to make sufficient progress in reducing alcohol related harms and death.